Spoilage potential characterization of Shewanella and Pseudomonas isolated from spoiled large yellow croaker (Pseudosciaena crocea). (4th December 2016) - Ge, Y.; Zhu, J.; Ye, X.; Yang, Y.
Abstract: Ten strains were isolated from a spoiled large yellow croaker ( Pseudosciaena crocea ). All of them were able to grow aerobically from 4 to 30°C, and reduce trimethylamine‐ N ‐oxide to trimethylamine (TMA) and produce H2 S except SB01, PF05 and PF07. Biochemical characterization and phylogenetic analysis of 16S rRNA gene showed that eight H2 S‐producing isolates were closely related to Shewanella baltica, and two isolates PF05 and PF07 were identified as Pseudomonas fluorescens and Pseudomonas fragi respectively. However, of the eight Shewanella, seven isolates cluster with S. baltica and one with Shewanella glacialipiscicola based on the analysis of the gyrB gene. Shewanella baltica also had the ability to produce biogenic amines, while two Pseudomonas had high activities of proteinase and lipase, and failed to produce TMA and biogenic amines. In spoilage potential evaluation, the TVB‐N value of S. baltica was significantly higher than that of Pseudomonas in sterile fish juice, although its growth was slower than Pseudomonas . Therefore, this work demonstrated that S. baltica was able to cause rapid and strong spoilage and was therefore identified as a specific spoilage organism in refrigerated P. crocea . Significance and Impact of the Study: Members of the bacterial genera Shewanella and Pseudomonas are widely known to be responsible for the specific spoilers in iced fish. Ten strains isolated from spoiled large yellow croaker ( Pseudosciaena crocea ) were identified as Shewanella baltica and Pseudomonas spp. S. baltica was demonstrated as the predominant spoiler in the refrigerated P. crocea due to its high metabolic activities. This work has generated baseline information for a better understanding of the role of various spoilage bacteria in chilled marine fish and for the control of contamination and growth of main spoilage bacteria to extend the shelf life of marine fish. Abstract : Significance and Impact of the Study : Members of the bacterial genera Shewanella and Pseudomonas are widely known to be responsible for the specific spoilers in iced fish. Ten strains isolated from spoiled large yellow croaker ( Pseudosciaena crocea ) were identified as Shewanella baltica and Pseudomonas spp. S. baltica was demonstrated as the predominant spoiler in the refrigerated P. crocea due to its high metabolic activities. This work has generated baseline information for a better understanding of the role of various spoilage bacteria in chilled marine fish and for the control of contamination and growth of main spoilage bacteria to extend the shelf life of marine fish.